A population-based survey of Chronic REnal Disease In Turkey--the CREDIT study - Suleymanlar, G.; Utas, C.; Arinsoy, T.; Ates, K.; Altun, B.; Altiparmak, M. R.; Ecder, T.; Yilmaz, M. E.; Camsari, T.; Basci, A.; Serdengecti, K. (Nephrology, dialysis, transplantation, 2011)
Chronic kidney disease (CKD) is a growing health problem worldwide that leads to end-stage kidney failure and cardiovascular complications. We aimed to determine the prevalence of CKD in Turkey, and to evaluate relationships between CKD and cardiovascular risk factors in a population-based survey. Medical data were collected through home visits and interviews. Serum creatinine, blood glucose, total cholesterol, triglycerides, HDL, LDL and uric acid were determined from 12-h fasting blood samples, and spot urine tests were performed for subjects who gave consent to laboratory evaluation. A total of 10 872 participants were included in the study. The final analysis was performed on 10 748 subjects (mean age 40.5 ± 16.3 years; 55.7% women) and excluded 124 pregnant women. A low glomerular filtration rate (GFR) (< 60 mL/min/1.73 m(2)) was present in 5.2% of the subjects who were evaluated for GFR, while microalbuminuria and macroalbuminuria were observed in 10.2% and 2% of the subjects, respectively. The presence of CKD was assessed in subjects who gave consent for urinary albumin excretion measurement (n = 8765). The overall prevalence of CKD was 15.7%; it was higher in women than men (18.4% vs. 12.8%, P < 0.001) and increased with increasing age of the subjects. The prevalence of hypertension (32.7% in the general population), diabetes (12.7%), dyslipidaemia (76.3%), obesity (20.1%) and metabolic syndrome (31.3%) was significantly higher in subjects with CKD than subjects without CKD (P < 0.001 for all). The prevalence of CKD in Turkey is 15.7%. Cardiovascular risk factors were significantly more prevalent in CKD patients.